PENAKSIR RASIO UNTUK RATA-RATA POPULASI MENGGUNAKAN KOEFISIEN VARIASI DAN KOEFISIEN KURTOSIS PADA SAMPLING GANDA - Angrianto, Heru; Adnan, Arisman; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses three type ratio estimators for population mean using coefficient of variation and coefficient of kurtosis on double sampling which is a review from the article of Singh et. al [Italian Journal of Pure and Applied Mathematics-N. 28(2011): 135-142]. The three estimators are biased estimators, then the mean square error of each estimator is determined. Estimator with the smallest mean square error is the most efficient estimator. Example is given at the end of discussion.